PENGARUH FIRM PERFORMANCE TERHADAP SUSTAINABLE PERFORMANCE DENGAN SUSTAINABILITY REPORT SEBAGAI VARIABEL MEDIASI (Studi Empiris Perusahaan yang terdaftar di Bursa Efek Indonesia tahun 2017-2020) - Muhammad Fawwaz Arkaan; Rr. Karlina Aprilia Kusumadewi (Diponegoro Journal of Accounting, 2023)
The purpose of this research is to examine the effect of firm performance on sustainable performance with a sustainability report as a mediating variable on Indonesian companies. The independent variable used in the test is firm performance which is measured using ROA and sustainable performance as the dependent variable is proxied using the ESG Score, and sustainability report as a mediating variable.This research used companies listed on the Indonesia Stock Exchange in 2017-2020 with a total sample of 201 samples. Sampling was based on a purposive sampling method that followed certain criteria. This research used companies listed on the Indonesia Stock Exchange in 2017-2020 with a total sample of 201 samples. Sampling was based on a purposive sampling method that followed certain criteria. Path analysis method is used in this study by using 2 equations, logistic regression and multiple regression.The results of this study indicates that firm performance has a positive effect on sustainable performance. Firm performance has a negative effect on the sustainability report. Sustainability report has a positive effect on sustainable performance. Simultaneously the firm performance variable has a positive effect on sustainable performance through the mediation variable of the sustainability report. Sustainability reports can mediate the effect of firm performance on sustainable performance.